2015
DOI: 10.4236/ojog.2015.56050
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Prolactin Levels in Patients Treated with Cabergoline for the Prevention of OHSS: Is Cabergoline Really Effective in Patients with High Risk of OHSS?

Abstract: Background: OHSS is a dangerous and potentially life-threatening condition for which many researchers look for new ways to treat. Aim: To determine the effectiveness of prophylactic cabergoline administration on prolactine levels in patients with high risk for ovarian hyperstimulation syndrome (OHSS). Material and Methods: 163 in vitro fertilisation (IVF) patients with high risk for OHSS were enrolled in the study. The criteria for inclusion were more than 15 oocytes retrieved at oocyte pick up. A standard ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, hCG and gonadotropins increase the amount of VEGF. 7 Vasoactive substances secreted by the ovaries increase mesothelial hyperpermeability and cause fluid leakage from the intravascular space to the third space. hCG, estradiol, prolactin, histamine, and prostaglandins are mediators that aggravate OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hCG and gonadotropins increase the amount of VEGF. 7 Vasoactive substances secreted by the ovaries increase mesothelial hyperpermeability and cause fluid leakage from the intravascular space to the third space. hCG, estradiol, prolactin, histamine, and prostaglandins are mediators that aggravate OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Oral et al determined the effect of cabergoline in IVF patients with high risk for OHSS. They concluded that prolactin levels in patients who were treated with cabergoline for the prevention of OHSS were low (Oral, Akpak, Karaca, & Savan, 2015). However, Elsersy et al in a randomized clinical trial study suggested that combined cabergoline and metformin could modulate cycle regularity and prolactin level in patients with PCOS and hyperprolactinemia (Elsersy, 2017).…”
Section: Oogenesis Stimulator Drugsmentioning
confidence: 99%